Power and voices of authority in the media narrative of Malaysian natives: combining corpus linguistics and discourse analysis approaches - Habibah Ismail,; Hazleena Baharun,; Hazlina Abdullah,; Siti Norzaimalina Abd Majid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Orang Asli is a group of indigenous people who live according to a set of lifestyle and belief system and speak the native language. Previous studies have found that the Orang Asli are mostly depicted in the news media as backwards and dependent on others (Marlina Jamal & Shakila Abdul Manan, 2016). Such stereotypical depiction is shared with other research undertaken in various countries, particularly those in Canada or Australia. While many of these studies analysed findings from the media and communication or socio-cultural perspectives, the present study examines the representation of Orang Asli in Malaysian news/media by focusing on the use of language, i.e. linguistic viewpoint. The examination undertaken in this study focuses on headlines and lead paragraphs of one of the most influential English language newspapers in Malaysia. This study demonstrates the synergy of two methodological approaches in linguistics namely critical discourse analysis and corpus linguistics. Our main findings show how Orang Asli is consistently depicted around stereotypical news narratives such as issues of land rights and other resources. We also found that the voices of Orang Asli leaders are overshadowed by other authorities such as the state government. Thus, this study contributes to shed light on the linguistics resources and language patterns used to portray the Orang Asli in Malaysian newspapers.